Crystal Structure, Spectroscopy, SEM Analysis, and Computational Studies of N-(1, 3-Dioxoisoindolin-2yl)benzamide. (6th September 2015) - Bülbül, Hakan; Köysal, Yavuz; Dege, Necmi; Gümüş, Sümeyye; Ağar, Erbil
Abstract : The compound N -(1, 3-dioxoisoindolin-2yl)benzamide, C15 H10 N2 O3, was prepared by the heating of an ethanolic solution of 2-hydroxy-1 H -isoindole-1, 3(2 H )-dione and 4-chloroaniline. The product was characterised using a combination of IR spectroscopy, SEM, and single crystal X-ray diffraction techniques. In addition to the experimental analysis, theoretical calculations were used to investigate the crystal structure in order to compare experimental and theoretical values. The X-ray diffraction analysis shows that the compound crystallises in the monoclinic space groupP 2 1 / c with the geometric parameters ofa = 13.5324 ( 11 ) Å, b = 9.8982 ( 8 ) Å, c = 9.7080 ( 8 ) Å, andβ = 95.425 ( 6 ) °. The crystal structure is held together by a network of N-H⋯O hydrogen bonds involving the carboxamide group.